Scientific projection of the School of Dentistry of the University of Medical Sciences of Havana - Ileana Bárbara Grau León; María de la Caridad Barciela González Longoria; Luis Soto Cantero (Editorial Ciencias Médicas, 2013)
The preparation of the scientific projection of the school of dentistry was described in this paper. The behavior of the scientific research in the institution based on documentary review and of three focal group sessions - made up of by members of the National Commission for this career, the Commission for granting scientific categories in dentistry and by professors who hold master´s degrees and PhDs in the school - was made to establish the scientific projections of the school for undergraduate and graduate education. This projection covers a curricular strategy of informatics research in undergraduate education; a curricular program for PhD in dentistry aimed at residents, professors and other dental specialists, and the preparation and implementation of an economic cooperation project. It also intends to contribute to the formation of research abilities in the graduates from this specialty, as well as to encourage formation of PhDs from earlier ages, and formation of foreign physicians, all of which will help to make contributions to the public health economics and will give international prestige to the institution. The scientific projection of the school of dentistry will be extended to 2015 including actions both at undergraduate and postgraduate levels, on the basis of seven strategic objectives. Keywords: scientific projection, research abilities, curricular PhD study, cooperation project.